2022
DOI: 10.7759/cureus.23972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C‐Reactive Protein-to-Albumin Ratio on Prognosis in Gastric Cancer Patients

Abstract: Purpose: The ratio of c-reactive protein-to-albumin (CRP/Alb) is a biochemical marker of systemic inflammatory response and has been associated with poor survival in cancer. The purpose of this study was to investigate the effect of CRP/Alb ratios on prognosis in gastric cancers. Methods: This study included a retrospective review of a total of 147 patients with locally advanced gastric cancer. Mean platelet volume (MPV) was analyzed statistically to find a prognostic relationship between monocyte/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We conducted a literature review on DEmRNAs in the PPI submodules of the three lesion stages (Tables S1–S5, Supporting Information [ 15–42 ] ). All the DEmRNAs were confirmed to be associated with cancers.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a literature review on DEmRNAs in the PPI submodules of the three lesion stages (Tables S1–S5, Supporting Information [ 15–42 ] ). All the DEmRNAs were confirmed to be associated with cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Blood samples were taken from all patients before surgery, and complete blood counts and biochemical parameters were measured. The calculation of the inflammatory indices is as follows: neutrophil to lymphocyte ratio (NLR) = neutrophil count/ lymphocyte count, platelet to lymphocyte ratio (PLR) = platelet count/lymphocyte count, SII = platelet count × neutrophil count/lymphocyte count, C-reactive protein (CRP) to albumin ratio (CAR) = CRP / albumin levels (Qiu, Zhang, and Chen, 2021;Uzunoglu and Kaya, 2023;Alkurt, 2022).…”
Section: Laboratory Parametersmentioning
confidence: 99%
“…Meanwhile, lymphocytes are instrumental in moderating tumor progression by producing cytokines and facilitating robust cellular immune responses (Ogiya, 2016). In this regard, many studies have shown that inflammatory indices such as NLR, PLR, and CAR can be used as prognostic biomarkers in patients with gastric cancer (Liang et al, 2020;Fu et al, 2021;Nechita, 2023;Alkurt et al, 2022). Previous studies have shown that CAR is a better prognostic indicator than mGPS (Lee, 2020;Liu, 2015).…”
Section: Figure 1 Diagnostic Performance Of Inflammatory Indices In P...mentioning
confidence: 99%
“…Accumulating evidence suggests that immune responses and inflammation influence tumor progression and metastasis ( 7 ). Many inflammatory blood-based indices, such as the neutrophil-to-lymphocyte ratio (NLR) ( 8 ), platelet-to-lymphocyte ratio (PLR), albumin-to-globulin ratio (AGR) ( 9 ), lymphocyte-to-monocyte ratio (LMR) ( 10 ), and C-reactive protein-to-albumin ratio (CAR) ( 11 ), are significant prognostic markers of different cancer types. The systemic inflammation response index (SIRI) is a novel hematologic parameter that was first proposed in 2016 ( 12 ) and is determined using the following formula: SIRI = (neutrophil × monocyte)/lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%